2017
DOI: 10.1021/acs.jpcc.7b02771
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochemical Phase Diagrams from Theory and Experiment: The Ni–Water System and Its Complex Compounds

Abstract: Electrode potential-pH (Pourbaix) diagrams provide a phase map of the most stable compounds of a metal, its corrosion products, and associated ions in solution. The utility of these phase diagrams is that they enable the assessment of electrochemical stabilities, for example, of Ni metal and its derived oxides, hydroxides, oxyhydroxides, against corrosion in aqueous environments. Remarkably, the Ni Pourbaix diagrams reported over the last 50 years are largely inconsistent with various electrochemical observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
179
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 75 publications
(215 reference statements)
14
179
0
Order By: Relevance
“…14 and Supplementary Note 4) confirmed that the conditioning did not change the chemical nature of C-Ni 1−x O. It is noteworthy that NiO is the thermodynamically stable phase in the potential window between 0 and −174 mV vs RHE according to the NiO pourbaix diagram 32 . The presence of overpotential of NiO reduction can further expand this potential window 8 .…”
Section: Synthesis and Structural Characterization Of C-doped Niomentioning
confidence: 70%
“…14 and Supplementary Note 4) confirmed that the conditioning did not change the chemical nature of C-Ni 1−x O. It is noteworthy that NiO is the thermodynamically stable phase in the potential window between 0 and −174 mV vs RHE according to the NiO pourbaix diagram 32 . The presence of overpotential of NiO reduction can further expand this potential window 8 .…”
Section: Synthesis and Structural Characterization Of C-doped Niomentioning
confidence: 70%
“…57,58 At the same time, the reduction potential of the dye anion is -0.70 V vs. NHE, 27,28 while the phase transition of the two-electron reduction of Ni 2+ to Ni 0 occurs at ca -0.4 V vs NHE. 58 Thus, a thermodynamic driving force of ca 0.3 V exists for nickel deposition, and Ni 0 is then expected to remain metastable ( Fig S10). This surface could then provide electrocatalytic sites for the observed generation of H2, similar to electrodeposited platinum metal in our previous work.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, there are many unavoidable technical or physical limitations imposed by experiment, for example, fierce combustion, defect contamination, uncontrollable/unmeasurable hydration, and solution filtering, which can result in large uncertainties (inaccuracies) in the extracted experimental Δ f G values. 31 Indeed, the Ti and Ni Pourbaix diagrams simulated using experimental Δ f G values are found to be inconsistent with various direct electrochemical phenomena, 31,32 which have been ascribed to the inaccuracies in the free energies of formation. Furthermore, some of the important compounds presenting potential and pH-dependent stabilities may exhibit structures that are poorly or difficult to characterize (e.g., NiOOH 31,33 ) or remain to be determined by experiment (e.g., Cr ).…”
Section: Introductionmentioning
confidence: 99%